The Influence of Green Marketing on Green Consumer Behavior at Fore Coffee, Alauddin Branch, Makassar - Muh Filah Alfarizi; Moh. Aris Pasigai; Aulia (GoodWill, 2026)
This study aims to analyze the effect of green marketing on green consumer behavior at Fore Coffee, Alauddin Branch, Makassar. The research adopts a quantitative approach using an infinite population model, with a sample size of 96 respondents determined through the Lemeshow formula. Primary data were collected using structured questionnaires distributed to consumers who had prior purchasing experience at Fore Coffee. The data were analyzed using Statistical Package for the Social Sciences (SPSS), including descriptive analysis, validity and reliability testing, and hypothesis testing. The findings indicate that green marketing has a positive and significant influence on green consumer behavior. This is evidenced by the calculated t-value (18.161), which exceeds the critical t-value (1.986), along with a positive regression coefficient of 0.763. These results suggest that the implementation of green marketing strategies—such as eco-friendly products, sustainable pricing, environmentally conscious distribution, and green promotional activities—can effectively enhance consumers’ environmental awareness and encourage sustainable consumption behavior. Furthermore, the study reveals that consumers generally respond positively to green marketing initiatives, although variations exist across specific indicators. The research contributes to the development of marketing and consumer behavior literature, particularly within the context of the coffee shop industry in Indonesia. Practically, the findings provide insights for business practitioners to design more effective green marketing strategies to strengthen sustainability efforts and influence environmentally responsible consumer behavior.